g(c(

f(c(s(

f(f(

f(

R

↳Dependency Pair Analysis

G(c(x, s(y))) -> G(c(s(x),y))

F(c(s(x),y)) -> F(c(x, s(y)))

F(f(x)) -> F(d(f(x)))

Furthermore,

R

↳DPs

→DP Problem 1

↳Remaining Obligation(s)

→DP Problem 2

↳Remaining Obligation(s)

The following remains to be proven:

**Dependency Pair:****G(c(***x*, s(*y*))) -> G(c(s(*x*),*y*))**Rules:**

g(c(*x*, s(*y*))) -> g(c(s(*x*),*y*))

f(c(s(*x*),*y*)) -> f(c(*x*, s(*y*)))

f(f(*x*)) -> f(d(f(*x*)))

f(*x*) ->*x***Dependency Pair:****F(c(s(***x*),*y*)) -> F(c(*x*, s(*y*)))**Rules:**

g(c(*x*, s(*y*))) -> g(c(s(*x*),*y*))

f(c(s(*x*),*y*)) -> f(c(*x*, s(*y*)))

f(f(*x*)) -> f(d(f(*x*)))

f(*x*) ->*x*

R

↳DPs

→DP Problem 1

↳Remaining Obligation(s)

→DP Problem 2

↳Remaining Obligation(s)

The following remains to be proven:

**Dependency Pair:****G(c(***x*, s(*y*))) -> G(c(s(*x*),*y*))**Rules:**

g(c(*x*, s(*y*))) -> g(c(s(*x*),*y*))

f(c(s(*x*),*y*)) -> f(c(*x*, s(*y*)))

f(f(*x*)) -> f(d(f(*x*)))

f(*x*) ->*x***Dependency Pair:****F(c(s(***x*),*y*)) -> F(c(*x*, s(*y*)))**Rules:**

g(c(*x*, s(*y*))) -> g(c(s(*x*),*y*))

f(c(s(*x*),*y*)) -> f(c(*x*, s(*y*)))

f(f(*x*)) -> f(d(f(*x*)))

f(*x*) ->*x*

Duration:

0:00 minutes